Rituximab plus leflunomide in rheumatoid arthritis: a randomized, placebo-controlled, investigator-initiated clinical trial (AMARA study). (5th March 2021) - Behrens, Frank; Koehm, Michaela; Rossmanith, Tanja; Alten, Rieke; Aringer, Martin; Backhaus, Marina; Burmester, Gerd R; Feist, Eugen; Herrmann, Eva; Kellner, Herbert; Krueger, Klaus; Lehn, Annette; et al.
Abstract: Objective: To investigate the efficacy and safety of rituximab + LEF in patients with RA. Methods: In this investigator-initiated, randomized, double-blind, placebo-controlled phase 3 trial, patients with an inadequate response to LEF who had failed one or more DMARD were randomly assigned 2:1 to i.v. rituximab 1000 mg or placebo on day 1 and 15 plus ongoing oral LEF. The primary efficacy outcome was the difference between ≥50% improvement in ACR criteria (ACR50 response) rates at week 24 ( P  ≤ 0.025). Secondary endpoints included ACR20/70 responses, ACR50 responses at earlier timepoints and adverse event (AE) rates. The planned sample size was not achieved due to events beyond the investigators' control. Results: Between 13 August 2010 and 28 January 2015, 140 patients received rituximab ( n  = 93) or placebo ( n  = 47) plus ongoing LEF. Rituximab + LEF resulted in an increase in the ACR50 response rate that was significant at week 16 (32 vs 15%; P  = 0.020), but not week 24 (27 vs 15%; P  = 0.081), the primary endpoint. Significant differences favouring the rituximab + LEF arm were observed in some secondary endpoints, including ACR20 rates from weeks 12 to 24. The rituximab and placebo arms had similar AE rates (71 vs 70%), but the rituximab arm had a higher rate of serious AEs (SAEs 20 vs 2%), primarily infections and musculoskeletal disorders. Conclusion: The primary endpoint was not reached, but rituximab + LEF demonstrated clinical benefits vs LEF in secondary endpoints. Although generally well tolerated, the combination was associated with additional SAEs and requires monitoring. Trial registration: EudraCT: 2009-015950-39; ClinicalTrials.gov: NCT01244958.